Śrī Jagannātha dibyasahasranāma : Oḍiāṭikā sahita - Rāutarāẏa, Gokuḷānanda (Nārāẏaṇī Sāhitya Kuṭīra ; Mukhya paribeshaka Bāṇīśrī, 1982)
Verse rendering of one thousand names of Jagannātha (Hindu deity)